Analisis Penggunaan Microsoft Excel dalam Pembukuan Keuangan Perusahaan: Sebuah Kajian Literatur (Jurnal Riset Manajemen dan Akuntansi, 2025)
Microsoft Excel has become a common tool used in corporate financial bookkeeping, especially for small and medium enterprises (SMEs). This article aims to analyze the use of Microsoft Excel in corporate financial bookkeeping through a literature review from various sources obtained through Google Scholar with the keyword "use of Microsoft Excel". The research method used is descriptive with a qualitative approach. The results of the study show that Microsoft Excel provides convenience in recording transactions, creating financial reports, and analyzing financial data. However, there are also limitations such as the risk of data input errors and reduced automation features compared to other accounting software. Therefore, although Microsoft Excel has significant benefits in financial bookkeeping, companies need to consider the needs and scale of operations in choosing the right tool.